From Garrison State to Nation-State political power and the Russian military under Gorbachev and Yeltsin - Moran, John P. (Praeger, 2002)
Why has the military not intervened in the post-communist political arena since the advent of democracy in Russia? Do lowered levels of professionalism actually lead to higher levels of intervention? Through a systematic exploration of professionalism within the Russian military, this study addresses these important questions. Moran suggests that by examining the notion of subjective fragmentation, both Gorbachev and Yeltsin utilized a highly effective, yet potentially troublesome, form of civil-military control. Findings that overall levels of praetorian behavior on the part of the Russian military have declined in this period, in spite of declining levels of military professionalism, challenge one of the most basic theoretical assumptions of civil-military relations.